2004
DOI: 10.1152/ajpregu.00655.2003
|View full text |Cite
|
Sign up to set email alerts
|

No effect of dietary calcium on body weight of lean and obese mice and rats

Abstract: Zhang, Qinmin, and Michael G. Tordoff. No effect of dietary calcium on body weight of lean and obese mice and rats. Am J Physiol Regul Integr Comp Physiol 286: R669-R677, 2004. First published December 18, 2003 10.1152/ajpregu.00655.2003.-Recent epidemiological and animal studies have led to the hypothesis that low dietary calcium intakes contribute to obesity. Here, we evaluated whether calcium influenced the body weight of normal-weight and obese rodents. All experiments involved female C57BL/6J mice or Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 50 publications
6
27
0
1
Order By: Relevance
“…These results are consistent with those reported in prior studies where calcium supplementation had no notable effect on body weight [43,44]. Contrary reports of a dose dependent diminutive effect of calcium on body weight in mice exist and this was attributed to a decline in the adipocyte fatty acid synthase activity and an elevation in lipolysis [45].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those reported in prior studies where calcium supplementation had no notable effect on body weight [43,44]. Contrary reports of a dose dependent diminutive effect of calcium on body weight in mice exist and this was attributed to a decline in the adipocyte fatty acid synthase activity and an elevation in lipolysis [45].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the skim milk was a rich source of calcium, whereas the fruit drink contained no calcium. However, studies to date do not support this proposal, with no observed effect of calcium on energy intake or appetite in humans (30) or energy intake in rats (31).…”
Section: Discussionmentioning
confidence: 96%
“…Zhang and Tordoff [19] found no effects of Ca manipulation in the diet on energy intake and body weight, and no simple relationship between calcitropic hormones and body weight. Boon et al [20] reported that dietary Ca content does not influence substrate metabolism, energy metabolism, or gene expression in proteins related to fat metabolism.…”
Section: Discussionmentioning
confidence: 98%